Topical ciclopirox olamine 1%: Revisiting a unique antifungal - Sidharth Sonthalia; Mahima Agrawal; V N Sehgal (Indian Dermatology Online Journal, 2019)
The injudicious use of antifungals, indiscriminate use of corticosteroids for instant relief, persistence of predisposing factors like sweat retention and uncontrolled diabetes, and emerging resistance to antifungals across the globe have rendered the management of an erstwhile simple infection, the superficial cutaneous mycoses highly complicated and tricky. Ciclopirox is an old yet efficacious, versatile, and safe topical antifungal of the hydroxypyridone family. Despite its numerous beneficial properties over the majority of other topical antifungals, it remains underutilized.